A new concept of instability and spatial patterns - Kučera, Milan; Klika, Václav; Fencl, Martin; Eisner, Jan (Nonlinear analysis: real world applications, 2026)
Non-standard notions of instability and spatial patterns are introduced and their robustness is proved. In fact, these notions correspond to what is really usually done in numerical computations or in a laboratory. Situations are described when our patterns evolve due to the newly introduced instability of the basic homogeneous steady state even if it is stable and even if heterogeneous stationary solutions do not exist.